2011
DOI: 10.1103/physrevb.83.104516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Fermi-surface shrinking on the optical sum rule in pnictides

Abstract: In this paper we investigate the effects of the band shifts induced by the interband spin-fluctuation coupling on the optical sum rule in pnictides. We show that, despite the shrinking of the Fermi surfaces with respect to first-principle calculations, the charge-carrier concentration in each band is almost unchanged, with a substantial conservation of the total optical sum rule. However, a significant transfer of spectral weight occurs from low-energy coherent processes to incoherent ones, with practical cons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
44
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 37 publications
(77 reference statements)
3
44
0
Order By: Relevance
“…If related to spin fluctuations, one could expect interband interactions to weaken at high T, as the strength of spin fluctuations decreases [11]. In Fig.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…If related to spin fluctuations, one could expect interband interactions to weaken at high T, as the strength of spin fluctuations decreases [11]. In Fig.…”
mentioning
confidence: 89%
“…These simulations allow to account for about half the experimental shift. Part of the expansion of the electron pockets could also be due to the weakening of the k-shift, as proposed in [11] for the model of interband interactions, or to an evolution of correlation effects.Single crystals of Ba(Fe 1−x Co x ) 2 As 2 were grown using a FeAs self-flux method and studied in detail by transport measurements [12]. ARPES experiments were carried out at the CASSIOPEE beamline at the SOLEIL synchrotron, with a Scienta R4000 analyzer, an angular resolution of 0.2…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…It is well known that the cuprates are single-band system where x 2 -y 2 band solely contributes to the electrodynamics. 7 Whereas the Fe-SCs are multiband systems, 60 spectral weight analyses of the Ba122 systems showed that the contribution of itinerant carriers extends to mid-infrared region in the form of featureless, incoherent conductivity. 16,37,61 The spectral weight associated with the itinerant carrier response can be used to quantify the impact of many-body effects.…”
Section: Methodsmentioning
confidence: 99%
“…(8)] (see Refs. [23,27] and the Supplemental Material [28]). As one can see, this is irrelevant on the Hall transport, while it contributes in part to the temperature dependence of the longitudinal conductivity, as discussed in Ref.…”
mentioning
confidence: 99%